The impact of body mass index on resource utilization and outcomes of children admitted to a pediatric intensive care unit. (January 2019) - Sharma, Kamal; Raszynski, Andre; Totapally, Balagangadhar R
Introduction: Obesity is associated with poor health outcomes but may be protective in intensive care unit patients. The objective of this study is to describe the characteristics of underweight, normal weight, and obese children, and to compare their length of stay, resource utilization, and mortality. Methods: The charts of 1447 patients who were admitted to a tertiary-level pediatric intensive care unit during 1 calendar year were reviewed. Patients were divided into three groups: underweight (<5th percentile), normal (5th–95th percentiles), and obese (>95th percentile). Body mass index for age percentile was used for children older than age 2 years, and weight-for-height percentile was used for children younger than age 2 years. Demographic data, Pediatric Index of Mortality 2 score, Pediatric Index of Mortality 2 risk of mortality, hospital mortality, hospital length of stay, the use and duration of ventilator support, hemodynamic support, and dialysis were determined. Results: Fifteen percent of children were underweight, while 61.5% were normal weight and 23.5% were obese; 54.9% of the patients were male. The overall mortality was 1.87%, with no significant difference between the three weight groups. The racial distribution, prevalence, and duration of invasive and noninvasive ventilation, and the use of vasopressors, central venous lines, and dialysis were similar between three groups. Tube feeding and parenteral nutrition were used more often in the underweight group. Pediatric intensive care unit and hospital lengths of stays were higher in underweight children. Underweight children were younger when compared to normal or obese children. Pediatric Index of Mortality 2 scores and Pediatric Index of Mortality 2 risk of mortality scores were higher in underweight children. Conclusion: There were no significant differences between the three weight groups in mortality. Underweight children were younger and sicker, and received tube feeding and parenteral nutrition more frequently.